(untitled) (Politeja, 2019)
Geopolitical Code – Theoretical and Methodological Concepts The article deals with geopolitical codes in relation to theoretical and methodological assumptions of social and political sciences. Geopolitical codes are considered in broad reference to the cultural and national codes of mythical narratives. The aim of this article is to transform cultural codes into analytical and methodological categories. The article includes an analysis of the concept of geopolitical code, its definition, and its classification as a set of social ideas. The text verifies the basic assumptions of geopolitical code: its structure, functions and possibilities of verification in the existing research methods of social, political and security sciences. The author also draws attention to the role of geopolitical codes in forming the state’s information security policy.